Dual color single particle tracking via nanobodies. (27th March 2015) - Albrecht, David; Winterflood, Christian M; Ewers, Helge
Abstract: Single particle tracking is a powerful tool to investigate the function of biological molecules by following their motion in space. However, the simultaneous tracking of two different species of molecules is still difficult to realize without compromising the length or density of trajectories, the localization accuracy or the simplicity of the assay. Here, we demonstrate a simple dual color single particle tracking assay using small, bright, high-affinity labeling via nanobodies of accessible targets with widely available instrumentation. We furthermore apply a ratiometric step-size analysis method to visualize differences in apparent membrane viscosity.